Trust and trustworthiness in nurse–patient relationships - Raeve, Louise de (Nursing philosophy, 2002)
This paper explores the nature of trust in nurse-patient relationships from the perspective of the patient's trust in the nurse and what might be said to then render such a relationship trustworthy, from the patient's point of view. The paper commences with a general examination of the nature of trust, followed by consideration of the nature of professional-patient relationships in healthcare, with emphasis on nurse- patient relationships in particular. The nature of this relationship is used to provide grounds for arguing, both morally and conceptually, that the nature of patients’ trust in those who nurse them is generally such that for the nurse to respond in a trustworthy way, she must care about her patients, not just for them. In arriving at this conclusion, the paper deliberately restricts its focus to nurse-patient encounters where patients are adults and a relationship, as opposed to a brief engagement between two people, can be said to have taken place. The context for this focus is public sector health care in the United Kingdom. In the text, gendered pronouns referring to doctors, nurses and patients are meant to be inclusive of both sexes.